Relative risk of all-cause mortality in patients with nontuberculous mycobacterial lung disease in a US managed care population. (December 2018) - Marras, Theodore K.; Vinnard, Christopher; Zhang, Quanwu; Hamilton, Keith; Adjemian, Jennifer; Eagle, Gina; Zhang, Raymond; Chou, Engels; Olivier, Kenneth N.
Abstract: Rationale: The risk of all-cause mortality of nontuberculous mycobacterial lung disease (NTMLD) in the United States (US) population is not well established. Objectives: This study aims to assess the public health burden of NTMLD in the US by comparing the relative risk of all-cause mortality in the NTMLD population with an age- and sex-matched cohort from the general population. Methods: Patients with physician claims for NTMLD (ICD-9 0.031; ICD-10 A31.0) were identified between 2007 and 2016 from a large US national managed care insurance plan covering approximately 15–18 million members annually. A control group with no NTMLD ICD-9 or 10 codes was randomly selected from the general population and matched 3:1 to the NTMLD sample according to birth year, gender, and insurance benefit coverage. The date of first NTMLD diagnosis of each patient was assigned to the matched controls as the index date. The Cox proportional hazard method compared survival between cohorts, adjusting for demographic factors and baseline comorbidities. Results: A total of 2005 patients with NTMLD and 6014 controls were identified, with a mean follow-up duration of 3.4 years and 3.7 years, respectively. The NTMLD group had substantially higher proportions of patients with asthma (23.3% versus 3.5%), bronchiectasis (36.5% versus 0.1%), COPD (52.0% versus 5.9%), arrhythmia (22.6% versus 6.5%), coronary artery disease (18.5% versus 6.6%), heart failure (11.9% versus 4.1%), and cancer (18.5% versus 5.0%). The unadjusted rate of all-cause mortality from the index date was 20.7 per 1000 person-years in the NTMLD group vs 5.6 per 1000 person-years in the control group (rate ratio = 3.73; 95% CI: 2.93–4.75). Multivariable Cox regression, adjusted for the above variables as well as all other important baseline covariates, showed a doubling risk of all-cause mortality (hazard ratio [HR] = 2.06; CI: 1.52–2.79; P < 0.001) in the NTMLD vs control group. Conclusions: All-cause mortality, adjusted for other factors, more than doubled with NTMLD compared with an age–sex–matched control group in a large US national managed care insurance plan. Highlights: This matched cohort study assessed mortality risk attributable to NTMLD. 2005 NTMLD patients and 6014 controls were identified from a US managed care plan. Unadjusted all-cause mortality for NTMLD patients was 20.7/1000 person-years. The fully adjusted all-cause mortality risk in NTMLD patients was more than double that of controls.